English-French Code Switching Used by The Main Character in The Movie Series Emily in Paris - Agustini, Ni Putu Ayu Devi; Savitri, Putu Weddha; Darmasetiyawan, I Made Sena (International Journal of Linguistics and Discourse Analytics, 2024)
Code-switching, a bilingual phenomenon in linguistics, refers to the practice of transitioning from one language to another, often between sentences. This practice is significant for understanding bilingual communication and identity expression. While code-switching can manifest across different languages, this study specifically focuses on English-French code-switching used by the main character in Emily in Paris. The research aims to categorize the types of code-switching observed and analyze the function of code-switching used by the main character in Emily in Paris. This research employs a qualitative research approach to comprehensively analyze instances of code-switching in the series. The primary method utilized for data collection involves documentation, utilizing note-taking techniques to thoroughly examine Emily in Paris based on both the movie script and subtitles. The collected data is analyzed through the theory of Appel and Muysken (2005), which classifies code-switching into three types: tag switches, intra-sentential switches, and inter-sentential switches. Additionally, the research explores six functions of code-switching: referential, directive, expressive, phatic, metalinguistic, and poetic functions. The analysis shows that Emily utilizes all three types of code-switching in her utterances, as well as various functions of code-switching. However, the predominant type observed is intra-sentential switching, where Emily inserts French terms into her English sentences. Concerning the functions of code-switching, Emily frequently employs the expressive function to emphasize a mixed identity by using English and French within a single conversation. While other functions such as referential, directive, phatic, metalinguistic, and poetic are also present in Emily’s speech, they occur less frequently. However, there are also instances of data that serve two functions of code-switching